Epidemic spread of Salmonella hadar in England and Wales. Issue 6221 (19th April 1980) - Rowe, B; Hall, M L; Ward, L R; de Sa, J D
Abstract : Salmonella hadar is now the second commonest serotype isolated from cases of food poisoning in England and Wales. Turkeys are the main reservoir of the organism and there is an urgent need to eradicate it from the breeding stocks; though this would be expensive, the cost must be balanced against the cost of treating the human disease.